Design Thinking Process of Leader Model for Nursing Educational Administrators Among the Coronavirus Disease 2019 Situation - Buachu, Thinnakorn; Tummeepukdee, Pimradar; Muangkaew, Prapaporn; Nuchasilp, Ravinun; Jaroensrimuang, Sirirak; Tassaneeyarat, Sirinna (Journal of The Royal Thai Army Nurses, 2022)
Nursing education leaders must be aware and creatively cope with the situation of the coronavirus disease 2019 epidemic, enabling leaders to learn and create a new paradigm in nursing education management in line with the new normal social era. When nursing education organizations face rapid changes, the role of a leader is challenging, complex, and extremely important. The design thinking process for leadership development will give nursing education administrators a new perspective on effective and effective management in order to maintain the quality of nursing education. Therefore, nursing education leaders must adopt a new educational management paradigm to cope with other emergencies that may arise in the future by developing leadership in emergency management, profession, and academy for the management of nursing education to be continued and appropriate in accordance with the situation through the design thinking process and main strategies to promote leadership development